1995
DOI: 10.1002/j.1460-2075.1995.tb00306.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a role of MEK and MAPK during signal transduction by protein kinase C zeta.

Abstract: Protein kinase C zeta (zeta PKC) is critically involved in the control of a number of cell functions, including proliferation and nuclear factor kappa B (NF‐kappa B) activation. Previous studies indicate that zeta PKC is an important step downstream of Ras in the mitogenic cascade. The stimulation of Ras initiates a kinase cascade that culminates in the activation of MAP kinase (MAPK), which is required for cell growth. MAPK is activated by phosphorylation by another kinase named MAPK kinase (MEK), which is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
193
1
1

Year Published

1997
1997
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(211 citation statements)
references
References 41 publications
16
193
1
1
Order By: Relevance
“…Additionally, PMA caused a rapid increase in ERK1 activity which paralleled the elevation in JNK activity. The involvement of the c-Raf-1-ERK signaling cascade in the modulation of gene expression by this phorbol ester is well established (Jones et al, 1994;Masuelli and Cutler, 1996;Whalen et al, 1997;de Vries-Smits et al, 1992;Bogoyevitch et al, 1995;Cai et al, 1997;Sozeri et al, 1992;Berra et al, 1995). These observations, combined with our unpublished ®nding that anisomycin, a selective activator of the JNKs (Bogoyevitch et al, 1995;Cano et al, 1994), does not increase u-PAR display, makes it likely that the propagation of the PMA stimulus to the nuclear transcriptional machinery regulating u-PAR expression is dependent on the cooperation of both JNK1-and ERK-dependent signaling modules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, PMA caused a rapid increase in ERK1 activity which paralleled the elevation in JNK activity. The involvement of the c-Raf-1-ERK signaling cascade in the modulation of gene expression by this phorbol ester is well established (Jones et al, 1994;Masuelli and Cutler, 1996;Whalen et al, 1997;de Vries-Smits et al, 1992;Bogoyevitch et al, 1995;Cai et al, 1997;Sozeri et al, 1992;Berra et al, 1995). These observations, combined with our unpublished ®nding that anisomycin, a selective activator of the JNKs (Bogoyevitch et al, 1995;Cano et al, 1994), does not increase u-PAR display, makes it likely that the propagation of the PMA stimulus to the nuclear transcriptional machinery regulating u-PAR expression is dependent on the cooperation of both JNK1-and ERK-dependent signaling modules.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, PMA induces ERK activity in a number of systems (Jones et al, 1994;Masuelli and Cutler, 1996;Whalen et al, 1997;de Vries-Smits et al, 1992;Bogoyevitch et al, 1995;Cano et al, 1995) and the co-expression of kinase-defective ERK1/ERK2 expression constructs inhibits the PMA-dependent stimulation of AP-1-regulated gene expression (Frost et al, 1994). Further, Protein Kinase C, the receptor for PMA, binds to and activates c-Raf-1 leading to ERK activation (Cai et al, 1997;Marquardt et al, 1994;Sozeri et al, 1992;Berra et al, 1995;Sauma and Friedman, 1996). On the other hand, several studies have demonstrated that JNK activity in the parallel signaling cascade is either not stimulated or only weakly activated by this phorbol ester Minden et al, 1994b;Hibi et al, 1993;Ludwig et al, 1996;Bogoyevitch et al, 1995;Cano et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that PKC acts downstream of Ras in the kinase cascade leading to mitogenesis (30,32). Stimulation of Ras initiates a kinase cascade that culminates in the activation of MAP kinase, which is required for cell growth and other cellular responses.…”
Section: Wt-vhl Blocks Pkc Pathways In Renal Cancersmentioning
confidence: 99%
“…We found ( Figure 5) that activated Ha-ras or v-raf (kindly provided by Dr J Moscat, CBM, Madrid, Spain) do not alleviate the PTEN-induced cell growth arrest, in agreement with out data obtained in Ki-ras transformed ®broblasts or in transformed murine keratinocytes (Figure 1a). Given that these constructs have been shown to e ciently induce MAPK/MEK cascades, at least in 3T3 cells (Cai et al, 1997;Berra et al, 1995), these results suggest that the ras/raf/MAPK mitogenic signals are not su cient to alleviate PTEN e ects, or alternatively, that PTEN acts also downstream of raf in this cascade. In this regard, it has been shown that activated MEK1 can overcome some PTEN induced e ects .…”
mentioning
confidence: 91%